Determinants of Audit fees by Brazilian Companies Publicly Traded - Borges, Victor Placeres (2017)
The studies on the determinants of audit fees in Brazil became possible with the mandatory disclosure of audit expenses in 2009. Thus, the objective of this research was to identify the determinants of the fees paid by Brazilian publicly traded companies to independent auditors in 2010 to 2014. The analysis took place through regression with data arranged in panel. Size, performance, complexity, audit firm size, adoption of corporate governance practices, audit rotation, industry and litigation risks have all been found to have an impact on the fees. Therefore, the aspects that can be used by companies for the purpose of information management or that require more auditing timefor signaling points of greater risks are highlighted. In addition, understanding the determinants allows companies to plan future expenditures with audit fees and assists regulators and inspectors in defining and comparing key determinants of firms for identifying abnormal payments. These results complement the research in Brazil, Australia, Bangladesh, Norway, Bahrain, England, Jordan, Kuwait, USA, Malaysia, Nigeria, Abu Dhabi, Italy and Indonesia.